EFFECTIVENESS OF LIFE SKILLS-BASED ADOLESCENT INTEGRATED HEALTH POST (POSYANDU) ON ADOLESCENT KNOWLEDGE AND ATTITUDES AT INGIN JAYA PUBLIC HEALTH CENTER, ACEH BESAR REGENCY - Fitriani, Fitriani; Rahmi, Rahmi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Adolescent Integrated Health Post as an innovative adolescent health service, offers a skill-based approach focusing on the development of adolescents' life skills—a key aspect in personal growth and attitudes. This research aims to evaluate the effectiveness of Life Skills-based Adolescent integrated services post on adolescents' knowledge and attitudes. The quasi-experimental method, One-Group Pretest-Posttest Design, compared conditions before and after the intervention, involving adolescent participation in the Posyandu program facilitated by healthcare professionals. Accidental sampling identified 21 respondents, adolescents with high school education (grades X-XII). Data collection utilized pre- and post-intervention questionnaires to measure adolescents' knowledge and attitudes related to health and life skills. Paired T-Test statistical analysis was employed on a single group of subjects using two different datasets, comparing pretest and posttest results. The research findings reveal that adolescent life skill knowledge, encompassing Empathy, Critical and Creative Thinking, Mental Health, and Substance Abuse, as well as life skill attitudes related to Self-Awareness, Empathy, Physical Activity, Non-Communicable Disease (NCD) Prevention, and Violence Prevention, show non-significant results (α ≥ 0.005). Conversely, adolescent life skill knowledge covering Self-Awareness, Decision-Making, Problem-Solving, Interpersonal Relations, Effective Communication, Stress Management, Emotional Regulation, Reproductive Health, Nutrition, Physical Activity, NCD Prevention, and Violence Prevention, along with life skill attitudes regarding Critical Thinking, Creative Thinking, Decision-Making, Problem-Solving, Interpersonal Relations, Stress Management, Effective Communication, Emotional Regulation, Reproductive Health, Mental Health and Substance Abuse, and Nutrition, exhibit significant results (α ≤ 0.005). These findings support the notion that a holistic approach through Life Skills-based Adolescent Integrated Health Post focusing on the development of adolescent life skills can be an effective strategy in enhancing adolescents' knowledge and attitudes related to health life skills. However, only a small fraction of skill aspects did not yield positive impacts on adolescents. The implications of this research can contribute to the development of similar community-level programs to support comprehensive adolescent development.